Inequity Aversion, Welfare Measurement and the Gini Index - Ulrich Schmidt; Philipp Christoph Wichardt (Center for Economic Studies and ifo Institute (CESifo), 2018)
Over the last decades, research in behavioural economics has demonstrated that individual welfare (utility), as relevant for economic decision making, depends not only on absolut but also on distributional aspects. Moreover, evidence is gathering that something similar holds for aggregate welfare, i.e. that GDP alone is an insufficient predictor for various supposedly welfare related variables on a societal level. This note shows that distributional concerns on an aggregate level can indeed be derived from distributional concerns on an individual level: integrating individual inequity aversion into a utilitarian social welfare function yields a simple welfare measure which comprises both GDP and income inequality as measured by the Gini index.
Keywords: D01; D63; 330; Gini index; inequality; welfare